The Citizens’ Assembly as an Institute of Municipal Law - Anastasiya G. Bykova (Сибирское юридическое обозрение, 2017)
The article analyzes the legal nature of the institute of municipal law - the assembly of citizens. From the position of theoretical jurisprudence, the Author analyzes the features of citizens’ assembly: normativity, content, principles, subject of legal regulation, subject composition (participants and organizers of citizens’ assembly), functions. Based on the analysis of municipal legal acts, a classification of citizens’ assemblies is carried out, as well as problems of the legal regulation of citizens' assemblies